The spiral ladder technique of facial nerve trunk identification during parotidectomy: A convenient roadmap for the beginners. (January 2022) - Rao, Vishal U.S.; Bylapudi, BhanuPrakash; Sinha, Piyush; Subash, Anand
Abstract: The intricate relationship between the facial nerve and the parotid gland makes the surgeries involving the gland challenging. Though several landmarks have been described to locate the nerve trunk, variations do exist due to the physical and racial characteristics of an individual. The spiral ladder technique described here uses multiple landmarks that appear in a stepwise manner as a beginner proceeds through the surgery as a road map to the nerve trunk. This simple adoption of a cluster of existing landmarks increases the certainty factor. This method may help beginners and in turn, reduce the chances of iatrogenic facial nerve injuries.